Optimalisasi Pengelolaan Wakaf Uang oleh Lembaga Keuangan Syariah – Pengelola Wakaf Uang di Indonesia - Yusuf; Syarif Hidayatullah; Surya Indrawan (Tasharruf : Journal of Islamic Economics and Business, 2021)
Islamic financial institutions that manage cash waqf are expected to be able to manage these assets in order to provide benefits in the form of welfare to the people. This study aims to analyze the management of waqf money made by Islamic financial institutions that earn mandate from the Ministry of Religion as the manager of cash waqf in Indonesia to date. This qualitative descriptive research was written based on on the literacy study. The conclusion of the research is that Islamic financial institutions – cash waqf managers need to optimize the management of cash waqf to developed in the form of Islamic banking products that are more welfare to society